Analysis of Vatavyadhi Samprapti – A Practical Perspective - Mohanta, Sarita; Das, Arun Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Ayurveda is one of the oldest medical systems comprising numerous medical concepts and hypotheses. Vatavyadhi is an important chapter described in all Samhitas. Vatavyadhi patients are increasing in day-to-day practice, so a clear understanding is necessary on its pathogenesis. Vatavyadhi occurs due to vitiation of Vatadosha. Vayu gets vitiated due to numerous factors staring from diet to various habits, used medicines, environmental changes, etc. Inside body Vayu gets vitiated and produces diseases either due to Dhatukshaya or Margavarodha. Materials and Methods: To analyze the Samprati (Pathogenesis) of Vatavyadhi from various Samhitas, contexts and the views of researchers are taken into consideration as method of the review. Discussion and Conclusion: Vatavyadhi is a group of special diseases which is produced due to aggravate Vata. Due to different etiological factors, Vata Prakopa occurs through Dhatukshaya and Margavarodha process which later produce Vatavyadhi. These pathological processes may be regarded as Vishista Samprati (Pathogenesis) of Vatavyadhi. During pathogenesis annoyed Vata may assemble with Pitta and Kapha, leading to modification of clinical features.